Development of a modulus of subgrade reaction model to improve slab-base interface bond sensitivity. Issue 14 (5th December 2020) - Saha, Sajib; Gu, Fan; Luo, Xue; Lytton, Robert L.
ABSTRACT: In the Pavement ME Design, the modulus of subgrade reaction ( k -value) is characterised by the dense liquid or Winkler model, which does not consider the interface bond within the supporting media. In this study, a modified k -value model was developed to take into account the shear interaction between concrete slab and base course. Formulation of the modified k -value model contained four steps: (a) correction of cross anisotropic base modulus; (b) development of a submodel for slab-base equivalent thickness; (c) development of a formula for slab-base interface shear bonding; and (d) determination of k -value using the calculated shear bonding and the deflection patterns of falling weight deflectometer (FWD). A large number of rigid pavement structural and strength properties and the corresponding FWD deflection patterns data were collected from the Long-Term Pavement Performance database and used to calculate the modified k -value. These were compared against the k -values using the existing 'backcalculated best-fit approach'. The results showed that the modified k -values changed significantly due to the consideration of cross anisotropy and slab-base interface bonding. Finally, an artificial neural network (ANN) approach was employed to predict the modified k -values for the given pavement structures, layer moduli and interface bonding ratios.